INSTITUTIONAL FACTORS FOR INCREASING ENTREPRENEURIAL ACTIVITY IN THE CONTEXT OF REGIONAL ECONOMIC TRANSFORMATION - Isakov , Axmadali (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article examines the institutional factors for increasing entrepreneurial activity under conditions of regional economic transformation. The study analyzes the impact of the regional business environment, quality of public administration, access to financial resources, digital services, legal guarantees, and infrastructural support on entrepreneurship development. The article substantiates that the stability of the institutional environment is an important factor for entrepreneurial activity, investment initiatives, and regional economic growth.